Wear failure mechanism analysis of self-lubricating fabric composites at high temperature. (22nd December 2022) - Yu, Mingming; Zhang, Min; Fang, Lin; Ren, Musu; Liang, Lei; Xie, Wang; Ma, Pibo
The friction and wear properties of self-lubricating fabric composites were closely related to fiber properties. In this paper, polyimide (PI), polyetheretherketone (PEEK), polyisophthalamide (PMIA) and cyclic aramid (Aramid III) fibers were selected as reinforcing fibers to compare and investigate the friction and wear properties of self-lubricating fabric composites at high temperature. The tribological behavior of self-lubricating fabric composites was evaluated by ball-on-disk friction test. The wear mechanism was investigated by scanning electron microscope and mechanical test. As a result, the composite with PI as warp and weft reinforcing fiber has outstanding wear resistance because of the higher modulus of PI fiber. Its wear rate is 1.29 × 10 −8  mm 3 /(N·mm). It shows that the stronger the rigidity of the reinforcing fiber at high temperature, the better the wear resistance of the composite. However, the friction coefficient of composites with PI as weft reinforcing fibers is about 0.8, which is much higher than that of composites with PMIA, PEEK and Aramid III as weft reinforcing fibers. Their friction coefficients are about 0.1. In addition, the self-lubricating fabric composites with different warp and weft reinforcing fibers were prepared as self-lubricating joint bearing liners to evaluate bearing applications.